Facile Direct C‐H Arylation Polymerization of Conjugated Polymer, PDCBT, for Organic Solar Cells. Issue 20 (18th August 2022) - Jang, Soo‐Young; Kim, In‐bok; Kim, Yunseul; Lim, Dae‐Hee; Kang, Hongkyu; Heeney, Martin; Kim, Dong‐Yu
Abstract: Direct arylation polymerization (DArP) is a synthetic method for conjugated polymers; in DArP, organometallic functionalization steps are omitted and there are no toxic byproducts. As a result, it is considered a more sustainable alternative compared to conventional methods such as Stille polymerization. To explore the possibility of DArP‐based polymers as donor materials in organic solar cells (OSCs), a series of conjugated polymers based on the structure of PDCBT (poly[2, 2''''‐bis[[(2‐butyloctyl)oxy]carbonyl][2, 2':5', 2'':5'', 2'''‐quaterthiophene]‐5, 5'''‐diyl]) are synthesized using DArP and Stille polymerization. By controlling the monomer concentration and reaction time in DArP, DArP‐5 with the highest M n (21.9 kDa) can be obtained and its optoelectronic properties, electrochemical properties, and microscopic molecular ordering are comparable to those of Stille‐based PDCBT (Stille‐P). Analysis of the polymer structure indicates no structural defects such as crosslinking from undesired β ‐coupling reactions in DArP‐5. Upon blending with the PC71 BM acceptor molecule, an increase in the crystallite size of DArP‐5 is also observed. In OSC devices with a polymer:PC71 BM bulk‐heterojunction photoactive layer, DArP‐5 demonstrates a comparable power conversion efficiency of 5.8% with that of Stille‐P (5.5%). These results prove that DArP is suitable for synthesizing PDCBT, and DArP‐based PDCBT can be used in OSCs as an alternative of Stille‐based one. Abstract : A series of conjugated polymers having chemical structures of PDCBT (poly[2, 2''''‐bis[[(2‐butyloctyl)oxy]carbonyl][2, 2':5', 2'':5'', 2'''‐quaterthiophene]‐5, 5'''‐diyl]) are synthesized using direct C‐H arylation polymerization (DArP). By optimizing the reaction conditions, PDCBT with similar molecular weight but less defect can be obtained from DArP compared with that from Stille polymerization. This is the first work in synthesizing PDCBT together with demonstrating its organic solar cell performances.